PENGARUH LABA, ARUS KAS, DAN MODAL KERJA TERHADAP PREDIKSI ARUS KAS OPERASI MASA DEPAN PADA PERUSAHAAN OTOMOTIF TERDAFTAR DI BEI - Sudarlan Sudarlan; Noor Fachman Tjetje; Pertiwi Dwita Sari (Jurnal Eksis, 2021)
The aim of this study is to provide empirical evidence regarding the effect of increases and decreases in earnings, operating cash flows and working capital in predicting future operating cash flows. The factors studied are operating profit, operating cash flow and operating working capital for the year. This study uses a quantitative approach, using secondary data from the financial statements of automotive companies listed on the IDX during the 2015-2020 period. Data analysis used the statistical method of multiple linear regression analysis using the SPSS program. The results of this study indicate that operating profit and operating cash flow have no significant effect, while working capital has a significant effect on predicting future cash flows. Keywords           : operating cash flow, profit, working capital, automotive, and prediction.